Single particle cryo-EM — an optimal tool to study cytoskeletal proteins. (October 2018) - Pospich, Sabrina; Raunser, Stefan
Highlights: Conservation and divergence of eukaryotic and prokaryotic cytoskeletal polymers. Species and isoform-specific structural features. Nucleotide-dependent conformational changes. Structural characterization of drug-binding. Specific challenges and advances in methodology. Abstract : Cytoskeletal proteins play essential roles in many cellular processes. Knowledge of their structures is important to understand their function and regulation. Since cytoskeletal polymers are difficult to crystallize, cryo-EM has been the predominant method of choice to study their structures. Recent advances in the methodology have enabled reconstructions at near-atomic resolution. In this review, we focus on novel insights gained from high-resolution cryo-EM structures of cytoskeletal polymers. These include eukaryotic proteins such as F-actin and microtubules as well as their prokaryotic homologues. The unprecedented high-resolutions allow identifying small molecules, including nucleotides and drugs, as well as subtle changes at interfaces that are key to complex processes, such as nucleotide hydrolysis in microtubules and actin filaments. While major methodological advances have already promoted the structural analysis of cytoskeletal polymers, there are still specific methodological challenges to overcome and many scientific questions remain to be answered.